Custis-Lee family papers - Custis, George Washington Parke, 1781-1857.; Law, Elizabeth Parke Custis, 1776-1832.; Lee, Ann Hill Carter, 1773-1829.; Lee, Anne Robinson McCarty, 1798-1840.; Lee, Arthur, 1740-1792.; Lee, Charles, 1758-1815.; Lee, Hannah Philippa Ludwell; Lee, Henrietta Bedinger, 1810-; Lee, Henry, 1691-1747.; Lee, Henry, 1756-1818.; Lee, Ludwell, 1760-1836.; Lee, Mary Bland, 1704-1764.; et al.
Correspondence, letterbooks, genealogical papers, notebooks, financial records, indentures, clippings, photographs, and other papers pertaining to slavery, agriculture in Virginia, mercantile and financial affairs, social life in Washington and Philadelphia, and to activities during the Revolution, Mexican War, and Civil War. Letterbook (1700-1825) of Richard Bland Lee contains correspondence of his grandparents, Henry and Mary Bland Lee, relating to family finances and business, trade with France, outfitting troops during the Revolution, founding of the new government, and the writing of the Constitution. Transcripts of correspondence (1811-1831) between David Bailie Warden, U.S. consul in Paris, and Elizabeth Parke Custis Law reflects diplomatic relations with France and naval and military affairs during the War of 1812. Robert E. Lee's correspondence (1830-1868) documents his military career as an engineer, his service in the Mexican War, and his role as general-in-chief of the Confederate armies. Correspondence (1837-1872) of his wife, Mary Randolph Custis Lee, pertains to family matters and her efforts to build a church in memory of her husband; her notebooks (1823) reflect the education of aristocratic young women in nineteenth century Virginia.
Prominent correspondents include John Adams, John C. Breckinridge, William Grayson, Nathanael Greene, Patrick Henry, John Jay, Thomas Jefferson, Joseph E. Johnston, Albert Miller Lea, Timothy Pickering, Mary Pinckney, William C. Rives, Winfield Scott, Samuel Harrison Smith, John Tyler, and Louis T. Wigfall.
Transcripts of correspondence of David Bailie Warden and Elizabeth Parke Custis Law made from originals in Maryland Historical Society (Baltimore). Also includes various transcripts and photocopies from other sources.
Members of the Custis and Lee families of Prince William and Westmoreland counties, Va. Principal individuals represented include George Washington Parke Custis (1781-1857), Arthur Lee (1740-1792), Charles Lee (1758-1815), Henry Lee (1756-1818), Richard Bland Lee (1761-1827), Richard Henry Lee (1732-1794), Robert E. Lee (1807-1870), William Lee (1739-1795), and William Henry Fitzhugh Lee (1837-1891).
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
The material now comprising the Custis-Lee family papers was originally processed and cataloged in separately titled collections of papers of Ann Hill Carter Lee, Anne Robinson McCarty Lee, Arthur Lee (1740-1792), Charles Lee (previously 2 collections), Hannah Philippa Ludwell Lee, Henrietta Bedinger (Mrs. H.I. or Mrs. H.J.) Lee, Henry Lee (1756-1818), Ludwell Lee (including letter from the marquis de Lafayette), Mary Custis Lee, Mary Randolph Custis Lee, Richard Bland Lee, Richard Henry Lee, Robert E. Lee, Thomas Lee, William Lee, William Henry Fitzhugh Lee, and the Custis family.
Keywords: Adams, John, -- 1735-1826 -- Correspondence; Breckinridge, John C. -- 1821-1875 -- Correspondence; Grayson, William, -- 1736-1790 -- Correspondence; Greene, Nathanael, -- 1742-1786 -- Correspondence; Henry, Patrick, -- 1736-1799 -- Correspondence; Jay, John, -- 1745-1829 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Johnston, Joseph E. -- 1807-1891 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert du Motier, -- marquis de, -- 1757-1834 -- Correspondence; Lea, Albert Miller, -- 1808-1891 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Monuments; Pickering, Timothy, -- 1745-1829 -- Correspondence; Pinckney, Mary Stead, -- approximately 1751-1812 -- Correspondence; Rives, William C. -- 1793-1868 -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; Smith, Samuel Harrison, -- 1772-1845 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Wigfall, Louis T. -- 1816-1874 -- Correspondence; Custis family; Lee family; Confederate States of America. -- Army; Agriculture -- Virginia; Diplomatic and consular affairs, American -- France -- Paris; Engineers; Memorials; Merchants -- Virginia; Mexican War, 1846-1848.; Military engineering; Slavery -- United States; Women -- Education -- Virginia -- 19th century; France -- Commerce -- United States; France -- Foreign relations -- United States; Philadelphia (Pa.) -- Social life and customs; Prince William County (Va.) -- Social life and customs; United States -- Foreign relations -- France; United States -- History -- 1783-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783.; United States -- History -- War of 1812.; Washington (D.C.) -- Social life and customs; Westmoreland County (Va.) -- Social life and customs